Achalasia Secondary to Submucosal Invasion by Poorly Differentiated Adenocarcinoma of the Cardia, Siewert II: Consideration on Preoperative Workup - Antonino Agrusa; Giorgio Romano; Giuseppe Frazzetta; Giovanni De Vita; Daniela Chianetta; Giuseppe Di Buono; Silvia Di Giovanni; Vincenzo Sorce; Gaspare Gulotta (Case Reports in Surgery)
Secondary achalasia due to submucosal invasion of cardia by gastric cancer is a rare condition. We report a case of pseudoachalasia, secondary to the involvement of gastroesophageal junction by poorly differentiated gastric cancer, initially mistaken as idiopathic form. We focus on the difficulty to establish differential diagnosis only on the basis of routine exams and we stress the necessity of “second level” instrumental exams; EUS in routine workup in selected patients should be considered. We support that routine workup based on history, clinical presentation, radiological and endoscopic findings, and certainly manometry could be insufficient for a correct differential diagnosis between primary and secondary forms in some patients.